4CPS-131 Differences in uk healthcare professionals' knowledge, attitude and practice towards infliximab and insulin glargine biosimilars. (2nd March 2018) - Aladul, M; Fitzpatrick, R; Chapman, S
Abstract : Background: Studies have shown that the relatively rapid introduction of biosimilars has resulted in a gap in knowledge among healthcare professionals. Purpose: To investigate knowledge, attitudes and practice of different healthcare professionals in the UK towards infliximab and insulin glargine biosimilars, and the factors influencing their prescribing. Material and methods: This was an anonymised, self-administered web-based survey among UK consultants, nurses and pharmacists registered in professional associations and societies between 8 August 2016 to 8 January 2017. Results: Responses were obtained from 234 healthcare professionals across dermatology, diabetology, gastroenterology and rheumatology specialties. Seventy-six per cent of consultants, 53% of nurses and 84% of pharmacists understood correctly what biosimilars were. Eighty-nine per cent of consultants and 96% of nurses weighted robust pharmacovigilance studies on biosimilars as the most important factor to increase their use of biosimilars, whereas 97% of pharmacists weighted NICE guidance as more important. Consultants and pharmacists weighted increased patient acceptability as the least important of all the factors. Nurses considered potential cost saving to the respondents' organisation as the less important of all the factors. When considering switching patients to a biosimilar, nurses had similar levels of concerns about safety and efficacy to initiation. In contrast, more consultants and pharmacists had concerns about safety and efficacy when switching patients compared to initiation. Conclusion: British consultants and pharmacists were well informed about, and had a comparable level of awareness of, biosimilars. Nurses were less well informed. Consultants, pharmacists and nurses differed in their opinion as to which factor would influence their use of biosimilars. All healthcare professionals had a higher level of concern in relation to switching compared to the initiation of biosimilars. References and/or Acknowledgements: Mohammed Aladul was sponsored by the Higher Committee for Education Development in Iraq No conflict of interest